Rancang Bangun Aplikasi Informasi Dan Keluhan Mitra PT Gojek Cabang Tangerang Berbasis Website - Resi Wicaksono (CV. Multi Kreasi Media, 2024)
he Gojek Tangerang Branch office located in Alam Sutera, South Tangerang, every day carries out service activities to its partners. However, the method applied still uses a manual service method where partners come to the nearest branch office to report problems faced by each partner and often result in buildup, making the atmosphere less comfortable and not conducive. Often partners get invalid or hoax information. To overcome this problem, an information system and partner complaints are needed that can handle partner complaints and provide valid information that can be accessed by partners, accompanied by complaint data management and information that can be accessed by staff. Making a web-based information and complaint system using the javascript language and ReactJs and NodeJs frameworks with the aim of making it easier for partners and staff to resolve partner complaints and provide valid information.